Innovation In Operations And Project Development Strategy at PHE ONWJ To Sustain The Business In Implementing Gross Split Production Sharing Contract - Sahroini, Nanang; Firman, Aries (Universitas Muhammadiyah Yogyakarta, 2018)
Oil & gas companies in Indonesia are facing a new challenge since the government changed the production sharing contract (PSC) from Cost Recovery scheme become Gross Split scheme through Ministerial Decree of ESDM No. 8/2017 and No. 52/2017, ‘Kontrak Bagi Hasil Gross Split’. The biggest challenge in new scheme is Company must bear all the capital cost and risk instead of Company and Government proportionally.In the way to get the research objectives in finding out key factors potential cause of failure the gross split implementation at PHE ONWJ and it’s strategy to avoid the failure, author performed the research by qualitative method referred to Creswell research methodology through individual interview of 10 experts in oil & gas industry. The scope of the paper is study literature, observation, individual interview, data analysis, finding and discussion, recommendation, and implementation plan.The research found out that key factor of potential failures the gross split implementation is the cost efficiency, which is driven by inefficiency activities, unmanaged risks, and unmanaged cash flow. If Company could not reach a certain amount cost efficiency that equivalent to expenditure ≤ 48% of total gross revenue, then definitely it leads to potential failure of Company operations business. Research analysis said that cost efficiency could be achieve when company succeed reducing the operation expenditure (OPEX) and capital expenditure (CAPEX) by performing innovation strategy such as changing the engineering design to fit-for-purpose, expanded procurement to new resources strategy, renegotiate existing contracts value, developing long term contracting strategies, improving contracts scope become very clear, generating work program prioritization, and improving the synergy of stakeholders.By doing the mentioned innovation strategies, company has obtained cost efficiency and generated positive cash flow for 1st year of gross split implementation. This is an early indication that the implementation of the gross split scheme could more likely be sustainable in PHE ONWJ.